Melatonin attenuates renal ischemia-reperfusion injury in nitric oxide synthase inhibited rats - Deniz, Esra; Colakoglu, Neriman; Sari, Aysel; Sonmez, Mehmet Fatih; Tugrul, Ibrahim; Oktar, Suleyman; Sahna, Engin (Elsevier Gmbh, Urban & Fischer Verlag, 2006)
Recent studies show that melatonin reduces the blood pressure (BP) and ischemia/ reperfusion (I/R)-induced damage. This study was designed to investigate the effects of melatonin on the renal I/R injury in rats given the nitric oxide synthase (NOS) inhibitor, N-omega-nitro-L-arginine methyl ester (L-NAME). After right nephrectomy, I/R was induced by occlusion of the left renal. vessels for 60 min, followed by 24h reperfusion. The administration of melatonin significantly attenuated BP in NOS-inhibited hypertensive rats. Malondialdehyde (MDA) levels, a stable metabolite of the free-radical-mediated lipid peroxidation cascade, were found to be significantly higher in the I/R group (3.48 +/- 0.2mg/l serum) than in the control group (2.69 +/- 0.2mg/l serum). L-NAME (40mgkg(-1) for 15 days)+I/R significantly increased the MDA levels compared to I/R alone. Melatonin administration to L-NAME rats significantly reduced the MDA values resulting from I/R. We also demonstrated that I/R, and especially L-NAME+I/R, lead to structural changes in the kidney and that melatonin attenuates these changes. These results suggest that metatonin reduces BP and I/R injury in NOS inhibited rats by L-NAME. (c) 2006 Elsevier GmbH. All. rights reserved.
Keywords: L-NAME; melatonin; hypertension; kidney; ischemia-reperfusion; malondialdehyde